2011
DOI: 10.1103/physrevb.84.075145
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal polynomial representation of imaginary-time Green’s functions

Abstract: We study the expansion of single-particle and two-particle imaginary-time Matsubara Green's functions of quantum impurity models in the basis of Legendre orthogonal polynomials. We discuss various applications within the dynamical mean-field theory (DMFT) framework. The method provides a more compact representation of the Green's functions than standard Matsubara frequencies and therefore significantly reduces the memory-storage size of these quantities. Moreover, it can be used as an efficient noise filter fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
233
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(234 citation statements)
references
References 33 publications
0
233
1
Order By: Relevance
“…These four-leg vertices, which are also central to the dynamical vertex approximation [37][38][39][40][41][42] (which was recently shown to be a simplified version of the QUADRuply Irreducible Local EXpansion (QUADRILEX), a method consisting of an atomic approximation of the four-particle irreducible functional [43]), can nonetheless only be obtained at a considerable computational expense and require a proper parametrization and treatment of their asymptotic behavior [44][45][46][47]. Consequently, it is not possible to use them routinely in multiorbital calculations (see, however, Refs.…”
Section: Beyond Gw+edmft: Comparison To Dual Bosons and Trilexmentioning
confidence: 99%
“…These four-leg vertices, which are also central to the dynamical vertex approximation [37][38][39][40][41][42] (which was recently shown to be a simplified version of the QUADRuply Irreducible Local EXpansion (QUADRILEX), a method consisting of an atomic approximation of the four-particle irreducible functional [43]), can nonetheless only be obtained at a considerable computational expense and require a proper parametrization and treatment of their asymptotic behavior [44][45][46][47]. Consequently, it is not possible to use them routinely in multiorbital calculations (see, however, Refs.…”
Section: Beyond Gw+edmft: Comparison To Dual Bosons and Trilexmentioning
confidence: 99%
“…8(b) compares our results with ones we obtained using a continuous-time QMC method to solve the twoorbital impurity problem. For the QMC, we employed a hybridization expansion algorithm in matrix form as implemented in the TRIQS package 17,18,63 . This allows us to perform calculations for the full rotationally-invariant Hamiltonian Eq.…”
Section: Two-band Hubbard Modelmentioning
confidence: 99%
“…Many different approaches have been proposed to tackle the problem. The most common ones are QMC 8,[15][16][17][18][19] , exact diagonalization (ED) [20][21][22][23] , and NRG [24][25][26] . QMC can efficiently handle multiple bands, but when formulated in imaginary time, it lacks high resolution of the spectral function.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for accurate and affordable realistic calculations, it is highly desirable to find compact representations of both imaginary time and Matsubara Green's functions. Recently, Boehnke et al [11] employed orthogonal polynomial representation of Green's functions to compactly express Hubbard Green's functions. Using this approach for realistic systems, we have shown that very accurate results can be obtained exploiting only a fraction of the original imaginary time grid points necessary to illustrate the energy spread of the realistic Hamiltonian.…”
Section: Introductionmentioning
confidence: 99%